Amphiphilic PdII‐NHC Complexes on 1, 3‐Alternate p‐tert‐Butylthiacalix[4]arene Platform: Synthesis and Catalytic Activities in Coupling and Hydrogenation Reactions. Issue 15 (28th February 2020) - Burilov, Vladimir A.; Gafiatullin, Mr. Bulat Kh.; Mironova, Diana A.; Sultanova, Elza D.; Evtugyn, Vladimir G.; Osin, Yuri N.; Islamov, Daut R.; Usachev, Konstantin S.; Solovieva, Svetlana E.; Antipin, Igor S.
Abstract : Herein we report the first example of amphiphilic Pd II –NHC complexes on the thiacalix[4]arene backbone in 1, 3‐alternate configuration. Relative catalytic activity of synthesized Pd II –NHC complexes in Suzuki–Miyaura coupling of haloarenes with phenylboronic acid was studied. A combination of micellar and metallocomplex catalysis was observed in Suzuki–Miyaura coupling upon going from pure DMF to water/DMF 3:1: the 2‐fold increase of conversion of 4‐bromoanisole unlike pure DMF was found. Interesting feature was found using chloroarene in DMF/water: the reaction selectivity changed from heterocoupling to homo coupling of phenylboronic acid. Pd II –NHC complexes demonstrated a high activity in model hydrogenation reaction of p ‐nitrophenol using sodium borohydride. The most lipophilic Pd II –NHC complex was found to be most active, which can be attributed with additional p ‐nitrophenol preconcentration in the aggregates due to larger hydrophobic capacity of macrocycle. Abstract : For the first time amphiphilic Pd(II)–NHC complexes on the thiacalix[4]arene backbone in 1, 3‐alternate configuration were synthesized. Relative catalytic activity of synthesized Pd(II)–NHC complexes in Suzuki–Miyaura coupling of haloarenes with phenylboronic acid and in model hydrogenation reaction of p ‐nitrophenol using sodium borohydride is discussed.